Empowering Charactered Education: The Impact of Educational Management on Islamic Guidance and Counseling for Vocational High School Students - Sabar Lamhot Tua Simatupang; Muhammad Arifin; Yusuf Olawale Owa-Oniren Uthman (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2024)
This research aims to analyse the role of educational management in field of Islamic guidance and counselling in creating character education for students at SMKN 1 Praya. The subjects in this study were school principals, educators, and education staff. While the object used is several students. The approach is qualitative, using a qualitative design and data collection methods including documentation, interviews, and observation. The steps of data reduction, data presentation, and conclusion-drawing were all included in the interactive model developed by Miles, Huberman, and Saldana for the analysis of the data. The findings indicate that the planning for guidance and counseling services is spot on, that the implementation of the services is carried out by guidance and counseling teachers in accordance with the plan because they are aware of their responsibilities, and that the implementation of the services is program-based. However, certain programs cannot be carried out effectively. It is not ideal for the principals to oversee the guidance and counseling services program. Since character education is not offered in every subject at every educational institution, this study differs from earlier studies in the field. The study's findings can serve as a guide for character development in all educational settings, particularly when it comes to practically integrating character education into all subjects and extracurricular activities